Physiological and transcriptomic responses to cold waves of the most cold-tolerant mangrove, Kandelia obovata - He, Shanshan; Wang, Xianxian; Du, Zhiyu; Liang, Pingping; Zhong, Yifan; Wang, Lin; Zhang, Yuan-Ye; Shen, Yingjia (Frontiers in Plant Science, 2023)
Mangrove forests inhabit tropical or subtropical intertidal zones and have remarkable abilities in coastline protection. Kandelia obovata is considered the most cold-tolerant mangrove species and has been widely transplanted to the north subtropical zone of China for ecological restoration. To explore mechanisms of cold tolerance in K. obovata, we manipulated the typical climate of cold waves in the north subtropical zone with cycles of cold/recovery and analyzed the physiological and transcriptomic responses of seedlings. We found that both physiological traits and gene expression profiles differed between the first and later cold waves, indicating K. obovata seedlings were acclimated by the first cold experience and prepared for latter cold waves. 1,135 cold acclimation-related genes (CARGs) were revealed, related to calcium signaling, cell wall modification, and post-translational modifications of ubiquitination pathways. We identified the roles of CBFs and CBF-independent transcription factors (ZATs and CZF1s) in regulating the expression of CARGs, suggesting both CBF-dependent and CBF-independent pathways functioned in the cold acclimation of K. obovata. Finally, we proposed a molecular mechanism of K. obovata cold acclimation with several key CARGs and transcriptional factors involved. Our experiments reveal strategies of K. obovata coping with cold environments and provide prospects for mangrove rehabilitation and management.